Timing and evolution of advanced conduction disturbances in patients with right bundle branch block undergoing transcatheter aortic valve replacement. Issue 10 (1st September 2020) - Muntané-Carol, Guillem; del Val, David; Junquera, Lucía; Faroux, Laurent; Delarochellière, Robert; Paradis, Jean-Michel; Mohammadi, Siamak; Kalavrouziotis, Dimitri; Dumont, Eric; Philippon, François; Rodés-Cabau, Josep
Abstract: Aims: This study sought to determine the timing and evolution over time of advanced conduction disturbances (CDs) in patients with baseline right bundle branch block (RBBB) undergoing transcatheter aortic valve replacement (TAVR). Methods and results: One hundred and ten consecutive patients with pre-existing RBBB were included (out of 1341, 8.2%). All arrhythmias during the hospitalization period were recorded. Follow-up was performed at 30 days, 1 year, and yearly thereafter. Conduction recovery and ventricular pacing percentage (VPP) was evaluated at 30 days in those patients with permanent pacemaker implantation (PPMI). Sixty-one (55.5%) patients suffered advanced CDs [97% complete or high-degree atrioventricular block (CHB/HAVB)], and the vast majority (98%) occurred within the first 3 days post-procedure (intraprocedural: 85%). Fifty-two (47.3%) patients had PPMI (vs. 11.0% in non-RBBB patients, P  < 0.001). Ventricular pacing percentage at 1 month was higher in patients with persistent-intraprocedural CHB/HAVB compared to those with transient-intraprocedural or post-procedural CHB/HAVB [99 (interquartile range, IQR 97–100)% vs. 72 (IQR 30–99)%, P  = 0.02]. Complete recovery (VPP < 1%) was observed in only one patient (2%) with CHB/HAVB. After hospital discharge, no symptomatic bradyarrhythmias or sudden death occurred within 30 days. Patients with pre-existing RBBB exhibited a higher risk of PPMI at 4-year follow-up (26% vs. 8% in non-RBBB patients, P  < 0.001). Conclusion: In patients with pre-existing RBBB, the vast majority of advanced CDs occurred within the 3 days following TAVR, and most did not recover at 1-month, particularly those with intra-procedural persistent CHB/HAVB. These results should help to determine the hospitalization length and timing of PPMI in RBBB patients undergoing TAVR.